From know-how to do-how the short and simple guide to making change happen - Corbet, Dave, 1961-; Roberts, Ian, 1957- (Nicholas Brealey Publishing, 2013)
In this highly practical book, Dave Corbet and Ian Roberts show just how quickly you can move forward once you recognize that the key to change is not your know-how understanding how to make change happen in theory but your do-how the shifts in behaviour that will deliver the changes you want, whether this be at home or work.